2013
DOI: 10.6004/jnccn.2013.0120
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Misuse and Abuse: Risk Assessment and Management in Patients with Cancer Pain

Abstract: The FDA's 2012 risk evaluation and mitigation strategy is a major step toward systematically reducing the inherent risks of chronic opioid therapy for pain, but does not distinguish between risks related to sources of pain. This article discusses the effect of risk mitigation in the treatment of cancer pain, with a focus on pretreatment screening and ongoing monitoring in this patient population that often requires pain management at some time during cancer treatment. Experience with screening, risk stratifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 43 publications
(64 reference statements)
0
85
0
4
Order By: Relevance
“…Psychiatric disease, which was identified as a warning sign for chemical coping in our study, also has been consistently reported as a warning sign for opioid-related problems in noncancer and cancer patients. 14,16,[20][21][22][23] Warning signs identified in our study may support further research to screen for chemical coping and develop appropriate interventions.…”
Section: Discussionmentioning
confidence: 61%
“…Psychiatric disease, which was identified as a warning sign for chemical coping in our study, also has been consistently reported as a warning sign for opioid-related problems in noncancer and cancer patients. 14,16,[20][21][22][23] Warning signs identified in our study may support further research to screen for chemical coping and develop appropriate interventions.…”
Section: Discussionmentioning
confidence: 61%
“…More frequent visits and short-term prescriptions may also help decrease risk in high-risk patients by reducing the amount of medication the patient has on hand at any given time [68]. Often, the decision for the provider is not a binary choice between prescribing opioids or not, but involves obtaining additional support, changing prescribing schedules, getting a family member to help with dispensing medications, or other techniques to reduce risk and enhance safety [69,70].…”
Section: Addiction Risk Management Recognition Of Addiction In Pain Pmentioning
confidence: 99%
“…When a patient shows aberrant behavior, the palliative medicine clinician has a responsibility to ensure that additional support and alternative methods are used to reduce risk and increase patient safety. 36 Opioid risk assessment: a process algorithm Te high risk of opioid medications must be considered when treating patients with pain in the setting of palliative medicine. However, with careful screening and information gathering, safe and efective pain control can be achieved in this complex population of patients (Figure).…”
Section: Management Of Addiction Riskmentioning
confidence: 99%